Properties of Cephalopod Skin Ommochromes to Inhibit Free Radicals, and the Maillard Reaction and Retino-Protective Mechanisms in Cellular Models Concerning Oxidative Stress, Angiogenesis, and Inflammation - Luján Lidianys María Lewis; Philipp Dörschmann; Charlotte Seeba; Tabea Thalenhorst; Johann Roider; Simon Bernard Iloki Assanga; Juan Carlos Gálvez Ruiz; Teresa Del Castillo Castro; Ema Carina Rosas-Burgos; Maribel Plascencia-Jatomea; Josafat Marina Ezquerra Brauer; Alexa Klettner (Antioxidants, 2022)
Ommochromes are pigments of invertebrates that exhibit oxidative stress protection. The aim of this study was to investigate ommochromes extracted from cephalopod’s skin for their ability to inhibit age-related-macular degeneration (AMD)-related factors such as H2O2-induced and iron-dependent oxidative stress (ferroptosis and erastin), accumulation of advanced glycation end-products (AGEs), as well as vascular endothelial growth factor (VEGF), and inflammatory cytokines (interleukin 6 and interleukin 8) secretion. As cell systems, we used primary porcine retinal pigment epithelium (RPE), human retinal pigment epithelium cell line ARPE-19 and uveal melanoma cell line OMM-1. In vitro, ommochromes produced an antiglycation effect by the inhibition of fructosylation reaction. The ommochromes showed protective effects against erastin- induced cell death in ARPE-19. In addition, in long-term stimulation (7 days) ommochromes decreased constitutively secreted VEGF, as well as interleukin 6 and interleukin 8 induced by Poly I:C in primary RPE. No relevant effects were detected in OMM-1 cells. The effects are dependent on the cell system, time of exposition, and concentration. This substance is of interest for further research concerning age-related macular degeneration.